Detection of Escherichia coli O157:H7 in Human patients Stool and Food by Using Multiplex PCR Assays Targeting the rfbE and the eaeAGenes compared with Detection by Biochemical Test and Serological Assay - Al-Dragy, Wathiq A; Baqer, Abeer A (Al-Nahrain Journal of Science, 2018)
Escherichia coli O157:H7 is an important food borne pathogen has been linked to foods of bovine origin and fresh produce. Rapid and sensitive identification of this dangerous pathogen is important for patient management and for prompt epidemiological investigations.This study aimed to detect Escherichia coli O157:H7 presence in samples from diarrhea patients, and food (imported beef and lettuce) and characterize by selective media, biochemical tests, latex agglutination test, and compared with PCR technique. during the period from September 2012 to February 2013 A total 120 samples were collected 50 from diarrhea patients and 70 food samples including (45 imported beef and 25 lettuce) All samples were screened to detect the presence of non-sorbitol fermenting colonies (NSF) on sorbitol Mac Conkey agar supplemented with Cefixime (C-SMAC). A total of 120 isolates, 22 (44%) from diarrhea patients, 18 (40%) from meat and 9 (36%) from lettuce were non-sorbitol fermenting, E. coli isolates were serotyped as E. coli O157:H7 by latex agglutination test, 10(20%) isolates of diarrhea patients, 7 (15.5%) isolates of meat and 5 (20%) isolates of lettuce, Results of the genetic diagnosis using polymerase chain reaction (PCR)with specific primers (eaeA and rfbE genes) by MPCR revealed that 10(20%) isolates of diarrhea patients5 (11.1%) isolate from meat and 5(20 %) of lettuce samples were positive. PCR has become a very rapid and reliable tool for the molecular diagnosis of E. coli O157. Ecoli O157: H7